Adaptation of the Self-Presentation Tactics Scale in a Mexican sample - González, Alan (2021)
Self-presentation allows people to display the desired image to belong to different groups and feel good; for this reason, it is important to count with proper tools for its measurement. The present study aimed to adapt the Self-Presentation Tactics Scale (SPTS) in adults from Mexico City and the metropolitan area with 626 volunteers from 18 to 60 years old. Results showed a 7-factor scale (52 % of the explained variance), with a Cronbach's Alpha of .90 and with convergent evidence of validity as it was correlated with the Bolino and Turnley Impression Management Scale and the Social Approval Need Scale. In conclusion, there are validity and reliability evidence in support of the use of the STPS. Additionally, our psychometric findings support the premise that some tactics can be configured differently depending on the cultural context, while others are presented similarly in multiple cultures.